(untitled) (Baltic Journal of Sport and Health Sciences, 2008)
Cortisol is a corticosteroid hormone produced by the zona fasciculata of the adrenal cortex in the adrenal gland. It plays vital roles in the body’s defense mechanisms when dealing with stress, as well as being important in blood glucose regulation. Regrettably, misconceptions regarding the actions of this hormone have been created around the sports and exercise arena. For example, cortisol most often is viewed as having a counter-productive role in exercise that can lead to a mal-adaptation to the exercise training process, due to the catabolic nature of this hormone with respect to protein turnover. Therefore, the intent of this article is to present an overview and to offer commentary on the necessary and critically important functions of cortisol during exercise, and in the adaptation process associated with exercise training. This is being done to specifically correct several of the misconceptions and misunderstandings that are portrayed within some literature (in particular on the Internet) regarding endocrine responses to exercise and exercise training. Keywords: Endocrine, hormones, glucocorticoids, sports.